Uganda : Technical Assistance Report-Report on Government Finance Statistics. (IMF Staff Country Reports; Country Report, 2017)
This Technical Assistance Report discusses technical advice and recommendations given by the IMF mission to the authorities of Uganda regarding compilation and dissemination of government finance statistics in accordance with the guidelines of Government Finance Statistics Manual 2001/14. The IMF mission, in collaboration with the Uganda Bureau of Statistics, the Bank of Uganda, and the Ministry of Finance, Planning, and Economic Development, produced a new institutional table that can be further reviewed, adopted, and used as a standard for the entire government of Uganda in the production of statistics. The IMF mission recommends that the government of Uganda continue to disseminate government finance statistics to the IMF and the East African Community and start disseminating a broader range of public sector debt statistics through the World Bank.